2014
DOI: 10.1111/mmi.12739
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella acquires ferrous iron from haemophagocytic macrophages

Abstract: SUMMARY Bacteria harbor both ferrous and ferric iron transporters. We now report that infection of macrophages and mice with a Salmonella enterica Typhimurium strain containing an inactivated feoB-encoded ferrous iron transporter results in increased bacterial replication, compared to infection with wild-type. Inactivation of other cation transporters, SitABCD or MntH, did not increase bacterial replication. The feoB mutant strain does not have an intrinsically faster growth rate. Instead, increased replicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
41
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 64 publications
1
41
0
Order By: Relevance
“…Hemophagocytosis was monitored by intracellular flow cytometry; macrophages that have engulfed erythrocytes stain positive for the erythrocyte marker TER119 (see Fig. S1 in the supplemental material) (23). At 18 h after infection with either bacterium, ca.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hemophagocytosis was monitored by intracellular flow cytometry; macrophages that have engulfed erythrocytes stain positive for the erythrocyte marker TER119 (see Fig. S1 in the supplemental material) (23). At 18 h after infection with either bacterium, ca.…”
Section: Resultsmentioning
confidence: 99%
“…Confocal microscopy has identified S. Typhimurium within hemophagocytes in the liver from 1 to 8 weeks postinfection (20). These cells may be a survival niche for S. Typhimurium because they provide the bacteria with iron (23). In addition, hemophagocytes appear to have an alternatively activated phenotype (7,21,24), suggesting that they are less adept at killing pathogens than other kinds of macrophages (25).…”
mentioning
confidence: 99%
“…Live Salmonella also induce the transformation of macrophages to hemophagocytes, these are phagocytes which have engulfed erythrocyte or leukocyte. In these cells, intracellular bacterial survival is greatly enhanced within hemophagocytes, due to a surplus of iron [47,48].…”
Section: Metal Starvation/toxicitymentioning
confidence: 99%
“…The bacteria reside within tissue macrophages (6,9) and hemophagocytic macrophages (10,56), which have phagocytosed intact erythrocytes and leukocytes. Recently, it has been observed that S. Typhimurium acquires iron from hemophagocytes (11).…”
mentioning
confidence: 99%